The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/ajmg.a.40517
|View full text |Cite
|
Sign up to set email alerts
|

The effect of steroid treatment on weight in nonambulatory males with Duchenne muscular dystrophy

Abstract: To describe the long‐term effect of steroid treatment on weight in nonambulatory males with Duchenne Muscular Dystrophy (DMD), we identified 392 males age 7–29 years with 4,512 weights collected after ambulation loss (176 steroid‐naïve and 216 treated with steroids ≥6 months) from the Muscular Dystrophy Surveillance, Tracking, and Research Network (MD STARnet). Comparisons were made between the weight growth curves for steroid‐naïve males with DMD, steroid‐treated males with DMD, and the US pediatric male popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The response to steroids may also play a role in protecting against a slower walk/run but also causing a higher BMI and short stature which may have functional benefits [22,23]. It is well documented in our cohort and in existing literature that steroid-treated boys with DMD have short stature from early in childhood and that finding is exacerbated with increasing age [10,11,42] As obesity becomes more severe, weight may have a greater effect on functional mobility, but we were unable to stratify the obesity category further according to obesity severity due to small sample sizes.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The response to steroids may also play a role in protecting against a slower walk/run but also causing a higher BMI and short stature which may have functional benefits [22,23]. It is well documented in our cohort and in existing literature that steroid-treated boys with DMD have short stature from early in childhood and that finding is exacerbated with increasing age [10,11,42] As obesity becomes more severe, weight may have a greater effect on functional mobility, but we were unable to stratify the obesity category further according to obesity severity due to small sample sizes.…”
Section: Discussionmentioning
confidence: 54%
“…Long-term corticosteroid 2 of 15 treatment is the mainstay therapy for DMD, with benefits including prolongation of ability to independently ambulate from 10 years in steroid-naïve boys to 13 years in steroid-treated boys [8,9]. Short stature and susceptibility to both over-and underweight are well documented in DMD [10,11]. Body mass index (BMI) is typically higher in both steroid-treated and steroidnaïve boys with DMD compared to typically developing children [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the W/A z-core was higher in G1 than G2 (p = 0.025), demonstrating that the weight changes resulting from the disease may not appear in early childhood. Lamb et al observed that longer duration and greater cumulative dose of glucocorticoids are significantly associated with lower W/A z-scores (Lamb et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…23,25 In addition, glucocorticoids (0.75 mg mg/kg per day of prednisone or 0.90 mg/kg/day of deflazacort) and prophylactic cardiac medication (lisinopril: 2.5 mg/day for those up to 40 kg, 5 mg/day for those ≥40 kg) 26 were assumed to be initiated at 8 years of age. We used published average weight data for patients with DMD treated with glucocorticoids 27 to estimate medication costs in combination with the recommended dose per body weight and unit price per dose.…”
Section: Calculation Of Costsmentioning
confidence: 99%